Optimalisasi Wakaf Produktif Melalui Pembangunan Rumah Pemberdayaan di Desa Cidokom - Nur Azizah; Rahmah Fitri Emiati; Heny Nur Afifah; Erlin Erlin; Rista Nindia Sari; Intan Diayu Wandira; Nurhayfa Nabilla; Shella Aklima Fatimah; Qoharuddin Ahmad Nafii; Az'zahra Putri Nabila; Khusnul Latifunnisa; Osanna Chikara Dewi (Universitas Maritim AMNI Semarang, 2024)
This service activity was carried out by students who carried out KKN at STF UIN Jakarta with a focus on raising and optimizing productive waqf funds for the construction of an Empowerment House in Cidokom Village. Through the Participatory Action Research (PAR) method, this activity involves students, lecturers, local communities and international volunteers in raising funds and implementing economic empowerment programs. As a result, the Empowerment House has become an educational and economic center that supports improving people's skills and independence, while also functioning as an integrated laboratory for students and lecturers. The success of this program shows that productive waqf can be a strategic instrument in building a sustainable and inclusive community economy.